2017
DOI: 10.1186/s40359-017-0176-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between pathologic subjective halitosis, olfactory reference syndrome, and social anxiety in young Japanese women

Abstract: BackgroundPathologic subjective halitosis is known as a halitosis complaint without objective confirmation of halitosis by others or by halitometer measurements; it has been reported to be associated with social anxiety disorder. Olfactory reference syndrome is a preoccupation with the false belief that one emits a foul and offensive body odor. Generally, patients with olfactory reference syndrome are concerned with multiple body parts. However, the mouth is known to be the most common source of body odor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…NA has also been used to study less known anxiety syndromes such as olfactory reference syndrome. Tsuruta et al [38] study revealed that SA may play a key role in the onset of fear to bodily odors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NA has also been used to study less known anxiety syndromes such as olfactory reference syndrome. Tsuruta et al [38] study revealed that SA may play a key role in the onset of fear to bodily odors.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1). Tsuruta et al [38] innovatively examined the association among SA symptoms and cognitive functioning and found that orienting attention to non-emotional material was linked to fear of social situations, which impacted the social experience by triggering avoidance of social behaviors. NA has also been used to study less known anxiety syndromes such as olfactory reference syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common disease in the oral and will bring some social anxiety to patients (Bicak, 2018). The main source of halitosis is the volatile sulfur-containing compounds (VSCs), produced by some bacteria, such as hydrogen sulfide, methyl mercaptan and so on, as well as some volatile aromatic compounds such as indole also playing a role in causing odor (Tsuruta et al, 2017). Halitosis is caused by bacteria in the mouth.…”
Section: Elimination Of Halitosismentioning
confidence: 99%
“…Although researchers have explored various aspects of halitosis, the research on the association of halitosis with psychology aspects has just begun. Many scholars have respectively adopted different psychological assessment scales to evaluate the impact of halitosis on psychological status, but with different focuses (Kishi, Abe, & Yonemitsu, 2005;Tsuruta et al, 2017;Zaitsu et al, 2011). Therefore, obtaining uniform and repeat- teeth, use of denture, orthodontic treatment, maxillofacial trauma/ surgery) and other socio-demographic status (such as employment, independent living, remission without medication, improved relationships, visits to dentist, marital status, living alone or with family, handicaps, etc.)…”
Section: Conceicao Et Al Assessed the Psychometric Properties Of Halmentioning
confidence: 99%